The More the Poorer? Resource Sharing and Scale Economies in Large Families - Rossella Calvi; Jacob Penglase; Denni Tommasi; Alexander Wolf (Institute of Labor Economics (IZA), 2020)
The structure of a family may have important consequences for the material well-being of its members. For example, in large families, an individual must share resources with many others, but she may benefit from economies of scale in consumption. In this paper, we study individual consumption in different types of households, with a focus on family structures that are common in developing countries. Based on a collective household model, we develop a new methodology to identify the intra-household allocation of resources and the extent of consumption sharing. We apply our methodology using data from Bangladesh and Mexico, and use the model estimates to compute poverty rates for men, women, and children. Contrary to existing poverty calculations that ignore either intra-household inequality or economies of scale in consumption, ours take into account both dimensions.
Keywords: D13; D11; D12; C31; I32; 330; collective model; household bargaining; resource shares; scale economies; Barten scales; indifference scales; poverty